The Relationship Of Characteristics Of Pregnant Women In Trimester 1 With The Event Of Hyperemesis Gravidarum In Shafaa Marwa Clinic, Batam City In 2020 - Syerly Ompu Prama; Sendy Pratiwi Ramadhani; Turiyani (Science Midwifery, 2022)
Hyperemesis gravidarum is severe nausea and vomiting during pregnancy which can cause various disturbances in the balance of the mother's body so that it can interfere with fetal growth. The exact cause of HEG is not known, but chronic increases in the hormones estrogen, progesterone and gonadotropins are thought to cause nausea and vomiting. The incidence of HEG at the Shafaa Marwa Clinic in Batam City is still quite high where in 2018 there were 21 people who experienced hypermesis gravidarum, in 2019 it fell to 16 people and in 2020 it increased again to 26 people. This study aims to determine the relationship between HEG and maternal age, parity, education and occupation. The method used is an analytical survey with a cross sectional approach. With a population of 187 pregnant women in the first trimester at the Shafaa Marwa clinic, 128 samples were taken using a simple random sampling technique. The results showed that there was a relationship between age and the incidence of HEG (p = 0.001), there was a relationship between gravida and the incidence of HEG (P = 0.001), there was no relationship between education and the incidence of HEG (P = 0.151 ) and there was no relationship between work and the incidence of HEG. (P = 0.935). There is a relationship between age, and parity with the incidence of HEG and there is no relationship between education and occupation with the incidence of hypermesis gravidarum. Suggestion It is necessary to hold an activity by health workers such as counseling about early detection of danger signs in young pregnancy, and others. Ongoing activities (posyandu) should be further improved so that they are able to control maternal health, especially for pregnant women.